1982
DOI: 10.1085/jgp.79.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Chemical energetics of slow- and fast-twitch muscles of the mouse.

Abstract: The energy utilization associated with contraction was measured in isolated slow-and fast-twitch muscles of the mouse at 20~ The extent of this utilization was estimated from either the extent of high-energy phosphate splitting occurring during contraction (the initial chemical change, A "-, Pinit) or from the extent of recovery resynthesis calculated from the observed oxygen consumption and lactate production occurring during the recovery period (recovery chemical resynthesis, A ~ P,~). For short tetani, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
361
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(399 citation statements)
references
References 26 publications
35
361
3
Order By: Relevance
“…Eliminating oxidative phosphorylation by anoxia permitted the use of PCr breakdown to measure the net cell ATP turnover that the mitochondria meets under resting, oxygenated conditions. Validation of this approach comes from a direct comparison of mitochondrial respiration under aerobic conditions vs. net ATP turnover during anoxia in isolated mouse muscles (27) and in vivo in rattlesnake tailshaker muscle (28). Anoxia of up to 30 min in intact muscle does not impact the activity of a key ATPase in resting muscle, Na-K-ATPase (29), and our measurements of glycolysis indicate a negligible contribution to ATP supply during the anoxic period (Ͻ8%).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Eliminating oxidative phosphorylation by anoxia permitted the use of PCr breakdown to measure the net cell ATP turnover that the mitochondria meets under resting, oxygenated conditions. Validation of this approach comes from a direct comparison of mitochondrial respiration under aerobic conditions vs. net ATP turnover during anoxia in isolated mouse muscles (27) and in vivo in rattlesnake tailshaker muscle (28). Anoxia of up to 30 min in intact muscle does not impact the activity of a key ATPase in resting muscle, Na-K-ATPase (29), and our measurements of glycolysis indicate a negligible contribution to ATP supply during the anoxic period (Ͻ8%).…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, activation of the myosin ATPases results in large differences in ATP turnover between muscle fiber types during exercise. Mouse muscles representing the extremes of fiber type composition, showed the same energetic fluxes at rest but greater than the 2-fold differences in flux during exercise at the same stimulation rate (27). Thus, eliminating contractile energetic differences by studying resting muscle reveals little difference in ATP turnover but does reveal a significant difference in mitochondrial O 2 uptake between muscles of the same subject.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand all fibres may be recruited at the start of exercise, however there may be a progressive increase over time in the neural stimulation of the type II fibres. As type II muscle fibres are less efficient than type I muscle fibres and posses an 18% lower phosphate produced to oxygen consumed ratio (P:O 2 ratio), 33,34 recruitment of these fibres would result in more oxygen consumption when required to maintain a given work rate. No correlation existed between the magnitude of the relative SC and the percentage of type IIx muscle fibres for the either the Tr or the RA groups, or when both groups were combined.…”
Section: Slow Component Of V á O 2 Kineticsmentioning
confidence: 99%
“…Type 11 have a lower oxidative efficiency than type I muscle fibers, with the P:O ratio found to be 18% lower in the former (47,48). It has been observed that UCP3 protein content is expressed decrescendo in Ilx>lla>1 muscle fiber types in both healthy and diabetic subjects (49) as weil as in endurance trained cyclists.…”
Section: Regulation Of Energy Expenditurementioning
confidence: 99%